STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER RELIGIUS SISWA DI MTs TANWIRUL QULUB LAMONGAN - Zubdatus Syarifah; Moh Eko Nasrullah; Atika Zuhrotus Sufiyana (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
Currently Islamic Religious Education in schools has faced various challenges in thisera of globalization, everyone knows about the importance of education in the life ofthis era, development is increasingly rampant both in terms of technology and otherfields, the goodness of the era of globalization is felt in terms of both young and old,no only that the negative side also has an impact, especially among young people whoare still amazed and want to find their identity. The focus of this study discusses thestrategy of Islamic religious education teachers in shaping students' moralknowledge through character education at MTs Tanwirul Qulub Lamongan. thestrategy of Islamic religious education teachers in shaping students' moral feelingsthrough character education at MTs Tanwirul Qulub lamongan. the strategy ofIslamic religious education teachers in shaping students' moral actions throughcharacter education at MTs Tanwirul Qulub lamongan, researchers used aqualitative approach with the type of case study. The application of this researchincludes the strategy of Islamic religious education teachers in shaping students'moral knowledge using the cognitive moral development approach, which is wherethis approach places more emphasis on cognitive activities, the strategy of Islamicreligious education teachers in shaping students' moral feelings using the actionapproach method, namely where the teacher provide opportunities to take actionsthat they consider good, the teacher's strategy in shaping students' moral actions usesthe habituation method, namely the teacher familiarizes students with activities thatcan foster better students' moral actions.